Application of triquetrous tadehagi herb extract in natural rubber processing and production method of natural whole-emulsion rubber

By using water-soluble antioxidants and cucurbit tea extract in natural rubber processing, the problem of oxidation of rubber during processing is solved, the antioxidant and mechanical properties of rubber are improved, and the storage time of the product is extended.

CN119505386APending Publication Date: 2025-02-25AGRI PRODS PROCESSING RES INST CHINESE ACAD OF TROPICAL AGRI SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803680.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the processing of natural rubber, non-glue substances such as carotene and tyrosine in the latex are oxidized under the action of oxidase, resulting in the formation of free radicals of rubber macromolecules, reducing antioxidant ability, and affecting the product's fixed extension stress, tensile strength and heat-resistant aging properties.

Method used

Water-soluble antioxidant and cucurbit tea extract are used to protect the rubber against oxality. The specific steps include mixing natural latex, water and water-soluble antioxidant for acid solidification to obtain latex blocks, then thinning, creping, granulation, and finally soaking and drying the rubber particles in the gurney tea extract solution to obtain natural whole milk rubber.

Benefits of technology

Through this method, natural whole-lact rubber has good antioxidant ability and mechanical properties, avoids the occurrence of oxidation, extends the storage time of the product, and improves the grade of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178654950000091
    Figure BDA0005178654950000091
  • Figure BDA0005178654950000092
    Figure BDA0005178654950000092
  • Figure BDA0005178654950000101
    Figure BDA0005178654950000101
Patent Text Reader

Abstract

The invention belongs to the technical field of natural rubber, and particularly relates to application of triquetrous tadehagi herb extract in natural rubber processing and a production method of natural whole-emulsion rubber. According to the production method of the natural whole-emulsion rubber provided by the invention, the water-soluble antioxidant is added in the solidification process of rubber processing, so that the oxidation resistance of latex is preliminarily improved; then the obtained colloidal particles are in contact with a desmodium triquetrum extract solution in the granulation process, residual acid generated during latex solidification is neutralized by utilizing the characteristic that the desmodium triquetrum extract is alkalescent, flavonoid and phenolic substances in the desmodium triquetrum extract have the anti-oxidation effect, and the colloidal particles soaking the desmodium triquetrum extract form a protective layer on the surface; and the anti-oxidation and anti-aging effects are achieved in the subsequent hot air drying process. According to the method provided by the invention, the performance of the rubber is well protected in the whole production process of the natural whole-emulsion rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rubber, and in particular relates to application of a bottle gourd tea extract in natural rubber processing and a method for producing natural full latex rubber. Background Art

[0002] Full latex is a standard rubber product of natural rubber. It is made of fresh natural latex from rubber trees. It is solidified into coagulation by acid coagulation. The coagulation is made into solid natural raw rubber products through production processes such as thinning, creping and dehydration, granulation and drying. During the coagulation process of latex, non-rubber substances such as carotene and tyrosine in the latex will be oxidized under the action of oxidase, which is easy to break the chain or escape from the main chain atoms or atomic groups, so that the rubber macromolecules form free radicals, resulting in reduced antioxidant capacity. In addition, the drying process uses hot air drying, and the strong hot air flow causes the rubber to be oxidized, which makes the rubber products have a decrease in indicators such as tensile stress, tensile strength, and heat aging resistance. Summary of the invention

[0003] In view of this, the present invention provides an application of a cucurbit tea extract in natural rubber processing and a method for producing natural whole latex rubber. The present invention uses a water-soluble antioxidant and a cucurbit tea extract to provide antioxidant protection for rubber. The natural whole latex rubber prepared according to the method provided by the present invention has good antioxidant capacity and mechanical properties.

[0004] In order to solve the above technical problems, the present invention provides application of bottle gourd tea extract in natural rubber processing.

[0005] The present invention also provides a method for producing natural full latex rubber, comprising the following steps:

[0006] The natural rubber latex, water and a water-soluble antioxidant are mixed and then acid coagulated to obtain a latex block;

[0007] The latex block is sequentially thinned, creped and granulated to obtain latex particles;

[0008] The rubber particles are immersed in a bottle gourd tea extract solution and then dried to obtain natural full latex rubber.

[0009] Preferably, the water-soluble antioxidant includes one or more of sodium ascorbate, sodium D-isoascorbate and glycine.

[0010] Preferably, the mass ratio of the dry rubber in the natural rubber latex to the water-soluble antioxidant is 100:0.2-2.

[0011] Preferably, the mass percentage of the Cucurbita foetida extract in the Cucurbita foetida extract solution is 0.3-1%.

[0012] Preferably, the soaking time is 0.05 to 4 minutes.

[0013] Preferably, the method for preparing the bottle gourd tea extract comprises the following steps:

[0014] The calabash tea is immersed in water for extraction to obtain an extract;

[0015] The extract is concentrated and mixed with ethanol for extraction to obtain an organic phase;

[0016] The organic phase is subjected to reduced pressure distillation to obtain the bottle gourd tea extract.

[0017] Preferably, the leaching temperature is 95-100° C., and the leaching time is 25-35 min.

[0018] Preferably, the acid solution comprises a formic acid solution or an acetic acid solution;

[0019] The mass concentration of the acid solution is 2.5-3.5%.

[0020] Preferably, the solidification time is 14 to 18 hours.

[0021] The present invention provides a method for producing natural full latex rubber, comprising the following steps: mixing natural latex, water and a water-soluble antioxidant and then acid coagulating to obtain a latex block; sequentially thinning, creping and granulating the latex block to obtain rubber particles; soaking the rubber particles in a solution of a gourd tea extract and then drying to obtain natural full latex rubber. In the present invention, a water-soluble antioxidant is added to perform preliminary antioxidant treatment on the rubber during the coagulation process, and then the gourd tea extract is used in the granulation process to improve its antioxidant property; the gourd tea extract is weakly alkaline and can neutralize the residual acid of the latex coagulation, and the gourd tea extract contains four triterpenoid substances, and the triterpenoid saponins formed can reduce the surface tension of the aqueous solution. The aqueous solution can produce persistent foam after strong shaking, has a surface activity like soap, can prevent the adhesion of the rubber particles, and plays the role of a separator. The gourd tea extract contains fourteen known flavonoids and fifteen known phenolic substances. The flavonoid compounds in the gourd tea extract have the ability of anti-oxidation and scavenging free radicals. The hydrogen atoms on the phenolic hydroxyl group can combine with peroxyl free radicals to generate flavonoid free radicals, and then react with other free radicals to terminate the free radical chain reaction. The phenolic substances in the gourd tea extract mainly prevent or inhibit chain initiation reactions and chain growth reactions by capturing peroxyl free radicals, thereby terminating the free radical chain reaction and achieving the purpose of preventing oxidation; through the reaction of its phenolic hydroxyl group with free radicals, stable free radicals are generated, thereby interrupting the chain propagation of the oxidation reaction. Therefore, the rubber particles soaked in the gourd tea extract form a protective layer on the surface, which plays an anti-oxidation and anti-adhesion role in the subsequent drying process. Under the joint action of the water-soluble antioxidant and the gourd tea extract, the invention reduces the generation of oxidation phenomenon of latex during processing, and improves the antioxidant property of natural full latex rubber. DETAILED DESCRIPTION

[0022] The invention provides application of a bottle gourd tea extract in natural rubber processing.

[0023] The present invention also provides a method for producing natural full latex rubber, comprising the following steps:

[0024] The natural rubber latex, water and a water-soluble antioxidant are mixed and then acid coagulated to obtain a latex block;

[0025] The latex block is sequentially thinned, creped and granulated to obtain latex particles;

[0026] The rubber particles are immersed in a bottle gourd tea extract solution and then dried to obtain natural full latex rubber.

[0027] The natural rubber latex, water and a water-soluble antioxidant of the present invention are mixed and then acid coagulated to obtain a latex block. As a specific embodiment of the present invention, the mixing comprises the following steps:

[0028] The natural latex and water are first mixed and then the water-soluble antioxidant is secondly mixed.

[0029] As a specific embodiment of the present invention, the first mixing may also include: removing impurities from the latex; the impurity removal method includes centrifugation. The present invention can remove impurities from the latex through centrifugation; the natural latex may be fresh latex of natural rubber.

[0030] As a specific embodiment of the present invention, the mass percentage of the dry glue in the natural latex can be 25-35%, and the mass percentage of the dry glue in the system after the first mixing can be 20-30%, which can be specifically 20%, 25%, 30% or 35%. The present invention has no special limitation on the first mixing, as long as it can be mixed evenly.

[0031] As a specific embodiment of the present invention, the water-soluble antioxidant may include one or more of sodium ascorbate, sodium D-isoascorbate and glycine, and may specifically be a mixture of sodium ascorbate and glycine, a mixture of sodium D-isoascorbate and glycine, sodium ascorbate, sodium D-isoascorbate or glycine; the mass ratio of sodium ascorbate to glycine in the mixture of ascorbic acid and glycine is 4:1, and the mass ratio of sodium D-isoascorbate to glycine in the mixture of sodium D-isoascorbate and glycine is 2:1. As a specific embodiment of the present invention, the mass ratio of the dry glue to the water-soluble antioxidant can be 100:0.2-2; when the water-soluble antioxidant is sodium ascorbate, the mass ratio of the dry glue in the natural rubber latex to the water-soluble antioxidant can be 100:0.5-2, specifically 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.3, 100:1.5, 100:2; when the water-soluble antioxidant is D -sodium isoascorbate, the mass ratio of the dry rubber in the natural rubber latex to the mass ratio of the water-soluble antioxidant can be 100:0.3-2, specifically 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.3, 100:1.5, 100:2; when the water-soluble antioxidant is glycine, the mass ratio of the dry rubber in the natural rubber latex to the mass ratio of the water-soluble antioxidant can be 100: When the water-soluble antioxidant is a mixture of sodium D-isoascorbate and glycine, the mass ratio of the dry rubber in the natural rubber latex to the water-soluble antioxidant is 100:0.2-2, which can be specifically 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.3, 100:1.5, 100:2; when the water-soluble antioxidant is a mixture of sodium D-isoascorbate and glycine, the mass ratio of the dry rubber in the natural rubber latex to the water-soluble antioxidant is 100:0.2-2, which can be specifically 100:0.2, 100:0.3, 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8 :0.8, 100:0.9, 100:1, 100:1.3, 100:1.5, 100:2; when the water-soluble antioxidant is a mixture of sodium ascorbate and glycine, the mass ratio of the dry rubber in the natural rubber latex to the water-soluble antioxidant is 100:0.4-2, and can be specifically 100:0.4, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.3, 100:1.5, 100:2.As a specific embodiment of the present invention, the water-soluble antioxidant can be mixed in the form of a solution, specifically: the first mixed system and the water-soluble antioxidant aqueous solution of the water-soluble antioxidant are mixed in the form of a second mixture; the water-soluble antioxidant aqueous solution is obtained by dissolving the water-soluble antioxidant in water, and the present invention has no special limitation on the amount of water, as long as it can be completely dissolved. The present invention has no special limitation on the second mixing, as long as it can be mixed evenly.

[0032] The purpose of adding a water-soluble antioxidant during the coagulation of natural latex is to protect the latex or latex block before it contacts the cucurbit tea extract. Since the water-soluble antioxidant can be miscible with the latex, the antioxidant can be evenly distributed in the latex, thereby making the latex show uniform antioxidant properties. In addition, sodium D-isoascorbate is a new type of biological food antioxidant, preservative, colorant, which can maintain the color and natural flavor of food, extend the shelf life, and has no toxic side effects; glycine is a constituent amino acid of the endogenous antioxidant reduced glutathione, and is a chain termination inhibitor. It contains active hydrogen and is easy to escape hydrogen atoms to generate free radicals. It can form stable products with free radicals generated by rubber to slow down oxidation; sodium ascorbate is an antioxidant for meat and other foods, and can also be used as a color preservative. It is an antioxidant that deactivates hydrogen peroxide. Its main function is that it is not easy to react directly with oxygen, but it is easy to react with the intermediate product of oxidation - hydroperoxide (ROOH) to generate stable products, so that ROOH does not decompose to produce active groups (deactivation). Water-soluble antioxidants can be washed away in subsequent processing steps such as thinning and creping.

[0033] As a specific embodiment of the present invention, the acid coagulation can be acid coagulation by mixing the second mixed system and the acid solution for the third time; the acid solution can include formic acid solution or acetic acid solution; the mass concentration of the acid solution can be 1-5%, which can be specifically 1%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. The present invention has no special limitation on the amount of the acid solution, and the amount of the acid solution is calculated according to the conventional calculation method in the art; a part of the acid solution is used to neutralize the ammonia in the latex; the other part is to make the rubber particles coagulate with each other and play a coagulation role. As a specific embodiment of the present invention, the third mixing can be carried out under stirring conditions, and the present invention has no special limitation on the stirring, as long as it can be mixed evenly.

[0034] As a specific embodiment of the present invention, the solidification time can be 8 to 20 hours, or 14 to 18 hours, and can be specifically 8 hours, 14 hours, 16 hours, 18 hours or 20 hours.

[0035] After obtaining the latex block, the present invention sequentially presses, crepes and granulates the latex block to obtain rubber particles. The present invention has no special requirements for the pressing, crepes and granulation, and the conventional methods in the art can be used.

[0036] After obtaining the colloid particles, the present invention soaks the colloid particles in a cucurbit tea extract solution and then dries to obtain natural full latex rubber. As a specific embodiment of the present invention, the cucurbit tea extract solution is obtained by mixing cucurbit tea extract and water; the mass percentage of cucurbit tea extract in the cucurbit tea extract solution can be 0.3-1%, and can be specifically 0.3%, 0.4%, 0.5% or 1%.

[0037] As a specific embodiment of the present invention, the preparation method of the gourd tea extract may include the following steps:

[0038] The calabash tea is immersed in water for extraction to obtain an extract;

[0039] The extract is concentrated and mixed with ethanol for extraction to obtain an organic phase;

[0040] The organic phase is subjected to reduced pressure distillation to obtain the bottle gourd tea extract.

[0041] As a specific embodiment of the present invention, the leaching temperature can be 95-100°C, specifically 95°C or 100°C; the leaching time can be 25-35min, specifically 25min, 30min or 35min. As a specific embodiment of the present invention, the leaching can also include: filtering the leached system to obtain the leaching solution; the present invention can repeat the steps of immersing the gourd tea in water, leaching and filtering, and the number of repetitions can be twice.

[0042] As a specific embodiment of the present invention, the concentration may be reduced-pressure concentration, and the mass of the concentrated product may be one tenth of the mass of the product before concentration.

[0043] As a specific embodiment of the present invention, the ethanol can be anhydrous ethanol or ethanol with a mass percentage of 90-98%, specifically 90%, 95% or 98%; the mass concentration of ethanol in the system after the extract is concentrated and mixed with ethanol can be 80-90%, specifically 80%, 85% or 90%.

[0044] As a specific embodiment of the present invention, the present invention recovers ethanol in the organic phase through vacuum distillation. The present invention has no special requirements for the vacuum distillation and can adopt conventional methods in the art.

[0045] As a specific embodiment of the present invention, the time for soaking the colloidal particles in the bottle gourd tea extract solution can be 0.05 to 4 minutes, specifically 3 seconds, 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 1 minute, 2 minutes, 3 minutes or 4 minutes.

[0046] As a specific embodiment of the present invention, the drying temperature may be 80-130°C, and may be specifically 85°C, 90°C, 95°C, 100°C, 110°C, 120 or 130°C.

[0047] The water-soluble antioxidant and gourd tea extract used in the present invention have no toxic side effects and do not pollute the environment; the water-soluble antioxidant is washed away by water in the subsequent process, does not remain in the rubber product, and does not damage the rubber performance; the gourd tea extract as an auxiliary agent has the functions of neutralizing the pH value of the rubber, preventing the adhesion of rubber particles during processing, and anti-oxidation and anti-aging, thereby improving the performance of the rubber. The solidified rubber block prepared according to the method of the present invention has no color variation, so that the product color is uniform and the grade of the product is improved; the full latex rubber prepared according to the method provided by the present invention has anti-mildew characteristics while maintaining the original performance of the rubber, thereby extending the storage time.

[0048] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0049] Example 1

[0050] Prepare the cucurbitacin tea extract solution as follows:

[0051] The bottle gourd tea is immersed in water and extracted at 100°C for 30 minutes, and then filtered to obtain an extract; the extraction and filtering steps are repeated twice, and the extracts obtained from the two extractions are mixed and concentrated under reduced pressure to one tenth of the mass before concentration, and the concentrated extract is mixed with ethanol with a mass concentration of 95% to make the mass concentration of ethanol in the system 85%, stirred evenly, allowed to stand and precipitate, and the supernatant organic phase is taken; the organic phase is subjected to reduced pressure distillation to recover ethanol to obtain a bottle gourd tea extract; the bottle gourd tea extract is mixed with water to obtain a bottle gourd tea extract solution with a mass concentration of 0.3%;

[0052] The ammonia content and dry rubber content in the fresh natural latex collected from the rubber plantation were detected and then centrifuged to remove impurities. The ammonia content in the natural latex was 0.21%, and the dry rubber content was 31.2%; 25 kg of the natural latex after impurities removal was first mixed with 5.2 kg of water, and the amount of D-sodium isoascorbate with a dry rubber content of 0.5% was calculated according to the dry rubber content to be 39 g, and the sodium D-sodium isoascorbate was dissolved in 1 kg of water and added to the latex after the first mixing (the mass ratio of sodium D-sodium isoascorbate to dry rubber in the latex was 0.5:100), and then the mixture was mixed for a second time under stirring and then allowed to stand for 30 minutes; 5.78 kg of formic acid solution with a mass concentration of 3% was added to the system after standing, and the mixture was stirred evenly and allowed to stand for 16 hours for acid coagulation to obtain a latex block;

[0053] The latex block is pressed thinly, creped and dehydrated, and granulated in sequence to obtain latex particles;

[0054] The rubber particles were immersed in a 0.3% gourd tea extract solution for 3 minutes, excess water was dripped off, and the rubber particles were dried in a forced air drying oven at 95° C. to obtain natural full latex rubber, which was recorded as sample 1.

[0055] Example 2

[0056] A natural full latex rubber was prepared according to the method of Example 1, except that the water-soluble antioxidant was replaced by a mixture of sodium ascorbate and glycine in a mass ratio of 4:1 from sodium D-isoascorbate; the amount of the water-soluble antioxidant added was replaced by a mass ratio of the water-soluble antioxidant to the dry rubber in the latex of 0.5:100 to a mass ratio of the water-soluble antioxidant to the dry rubber in the latex of 0.4:100;

[0057] The mass concentration of the bottle gourd tea extract solution was changed from 0.3% to 0.4%; the prepared natural full latex rubber was recorded as Sample 2.

[0058] Example 3

[0059] A natural full latex rubber was prepared according to the method of Example 1, except that the water-soluble antioxidant was replaced by a mixture of sodium D-isoascorbate and glycine in a mass ratio of 2:1 instead of sodium D-isoascorbate.

[0060] The mass concentration of the bottle gourd tea extract solution was changed from 0.3% to 0.5%; the prepared natural full latex rubber was recorded as Sample 3.

[0061] Example 4

[0062] The cucurbit tea extract was prepared according to the method of Example 1; the cucurbit tea extract was added to the collection pool in the granulation step so that the mass percentage of the cucurbit tea extract in the collection pool water was 1%;

[0063] This example scales up the experiment to the ton level, uses production line equipment to conduct the experiment, and the resulting samples are close to actual production;

[0064] Fresh natural rubber latex was collected from rubber plantations, and its ammonia content and dry rubber content were tested and then centrifuged to remove impurities. The ammonia content of natural rubber latex was 0.23%, and the dry rubber content was 30.7%.

[0065] 1000 kg of natural latex after impurity removal and 200 kg of water are first mixed, and the amount of D-sodium isoascorbate with a dry rubber content of 0.3% is calculated according to the dry rubber content to be 921 g; the D-sodium isoascorbate is dissolved in 28 kg of water and added to the latex after the first mixing (the mass ratio of the D-sodium isoascorbate in the latex to the dry rubber is 0.3:100); the mixture is mixed for a second time under stirring and then allowed to stand for 30 min; 249 kg of formic acid solution with a mass concentration of 3% and the second mixed latex are placed in a coagulation tank in parallel, mixed evenly and allowed to stand for coagulation for 16 hours to obtain a latex block;

[0066] The solidified latex blocks are pressed, creped, dehydrated and granulated in sequence. The obtained rubber particles fall into a collection pool and come into contact with the gourd tea extract solution for 3 to 6 seconds. They are then pumped into a drying car by a liquid-solid separation pump, allowed to drip, and pushed into a drying room for drying at 95°C to obtain natural full latex rubber, which is recorded as sample 4.

[0067] Example 5

[0068] Natural whole latex rubber was prepared according to the method of Example 4, except that the water-soluble antioxidant was replaced by sodium ascorbate instead of sodium D-isoascorbate; the amount of water-soluble antioxidant added was replaced by a mass ratio of water-soluble antioxidant to dry rubber in latex of 0.3:100 instead of a mass ratio of water-soluble antioxidant to dry rubber in latex of 0.5:100; and the prepared natural whole latex rubber was recorded as Sample 5.

[0069] Comparative Example 1

[0070] Fresh natural rubber latex collected from rubber plantations was tested for ammonia content and dry rubber content. The ammonia content and dry rubber content of the natural rubber latex were 0.21% and 31.2% respectively. The natural rubber latex was subjected to centrifugal sedimentation to remove impurities in the latex. 10 kg of the latex after impurity removal was taken out, diluted with 2.48 kg of water to a dry rubber content of 25%, and then mixed evenly with a formic acid solution with a mass concentration of 3% (the amount of neutralizing acid and coagulating acid required was calculated according to the ammonia content in the natural rubber latex, and the amount of acid was 2.31 kg), and allowed to stand for 16 hours for acid coagulation. The latex blocks obtained by coagulation were pressed, creped and dehydrated, and granulated in sequence to obtain rubber particles.

[0071] The rubber particles were placed in a forced air drying oven and dried at 95°C to obtain full latex rubber, which was recorded as control sample 1.

[0072] Test Example 1

[0073] The colloid particles in Comparative Example 1 were divided into 6 groups, each with 30g, and used for the soaking isolation effect experiment of Cucurbita tea extract with different concentrations; the Cucurbita tea extract prepared in Example 1 was added with water to prepare Cucurbita tea extract solutions with mass concentrations of 0%, 0.1%, 0.2%, 0.3%, 0.4% and 0.5%, respectively, and the 6 groups of colloid particles were respectively placed in the above-mentioned Cucurbita tea extract solutions and soaked for 3min, and then taken out for isolation effect test, and marked as isolation sample 1, isolation sample 2, isolation sample 3, isolation sample 4, isolation sample 5 and isolation sample 6 in sequence.

[0074] The isolation effect of full latex rubber is tested as follows:

[0075] Take a commercially available 500mL syringe, fix it on the iron stand with a clip, pull out the syringe push rod, and put the isolated samples 1 to 6 into the syringe respectively. The excess water will be discharged from the injection port. Install the push rod and push it until the colloid particles are compacted. Then press on the 2kg weight and maintain the pressure for 5 minutes. Remove the weight, pull out the push rod and pour out the colloid particles. Use tweezers to check the adhesion of the colloid particles. The results are shown in Table 1.

[0076] Table 1 Adhesion of the particles of isolated samples 1 to 6

[0077]

[0078] It can be seen from Table 1 that the effect of the bottle gourd tea extract as a release agent for rubber particles is very obvious. When the mass concentration of the bottle gourd tea extract solution reaches more than 0.3%, an ideal effect is achieved.

[0079] The effects of water-soluble antioxidants and dosage on improving the antioxidant properties of natural rubber latex were tested as follows:

[0080] During the coagulation process of latex, non-rubber substances such as carotene and tyrosine in latex will be oxidized under the action of oxidase, and the surface phenomenon is that the surface color of the rubber block becomes darker. It is easier to observe if the rubber block is pressed into a film.

[0081] The experiment uses latex with an ammonia content of 0.21% and a dry glue content of 31.2%, and conducts 5 groups of experiments, each with 8 samples, and each sample has 300g of latex. The water-soluble antioxidant and latex are mixed according to the mass ratio of the water-soluble antioxidant to the dry glue in the latex of 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, and 1:100; the calculated usage of the water-soluble antioxidant in each group is 0.0936g, 0.1872g, 0.2808g, 0.3744g, 0.468g, 0.5616g, 0.6552g, and 0.936g, respectively. Water-soluble antioxidants were weighed separately and added evenly to the latex. 69.39 mL of 3% formic acid solution was added to each experimental group sample and allowed to stand for 16 h to solidify. The samples were then pressed into thin films and left for 24 h. The color changes of the films were observed. If there was a change, it was recorded as "color change", and if there was no change, it was recorded as "unchanged". The results are listed in Table 2.

[0082] Table 2 Amount of water-soluble antioxidants added and their effects

[0083]

[0084]

[0085] It can be seen from Table 2 that the selected water-soluble antioxidants can play an antioxidant role at appropriate concentrations. When glycine is used alone as an antioxidant, the effect is not obvious, but when used in combination with other antioxidants, the amount of antioxidant used can be reduced.

[0086] The physical and chemical properties and vulcanization performance tests were performed on the samples prepared in Examples 1 to 5 and Comparative Example 1 according to the following method. The rubber vulcanization performance test was performed according to the ACS I pure rubber formula specified in NY / T 1403-2007 (100.00 parts of natural rubber, 6.00 parts of zinc oxide, 3.50 parts of sulfur, 0.50 parts of stearic acid, and 0.50 parts of MBT). The results of the physical and chemical properties test are shown in Table 3, and the vulcanization performance test is shown in Tables 4 and 5.

[0087] Table 3 Physical and chemical properties of samples prepared in Examples 1 to 5 and Comparative Example 1

[0088]

[0089]

[0090] From the data in Table 3, it can be seen that the ash content of the natural rubber samples prepared in Examples 1 to 5 is not increased compared with that in Comparative Example 1, indicating that the water-soluble antioxidant is washed away by water in the subsequent process and does not remain in the raw rubber. PRI has increased, indicating that the weakly alkaline gourd tea extract neutralizes the acidity of the raw rubber, and a protective layer is formed on the surface of the rubber particles during the soaking process, which improves the thermal oxidation aging resistance of the rubber during the drying process. The accelerated storage test of the samples of Examples 1 to 5 and the control samples by the national standard MV method and the national standard P0 method shows that the antioxidant performance of the samples of the examples is significantly better than that of the control samples.

[0091] Table 4 Vulcanization characteristic parameters of samples of Examples 1 to 5 and Comparative Example 1

[0092]

[0093] Note: 10 / minStart time of vulcanization reaction (min);

[0094] t 90 / minThe time for the vulcanization reaction to reach 90% completion (min);

[0095] M H / dN·mThe maximum torque displayed by the sulfur analyzer (dN·m);

[0096] M L / dN·mThe minimum torque displayed by the sulfur analyzer (dN·m);

[0097] ΔM / dN·m: The difference in torque (dN·m). The larger the value, the higher the degree of vulcanization.

[0098] Table 5 Mechanical properties of the vulcanized rubber of Examples 1 to 5 and Comparative Example 1

[0099]

[0100]

[0101] The data in Table 4 show that the example group has a shorter scorch time (t 10 ), which is because the alkaline isolating agent (cucurbit tea extract solution) neutralizes the residual acid in the rubber, reducing the inhibitory effect of the acid on the decomposition process of the accelerator M (2-mercaptobenzothiazole), resulting in t 10 Compared with M H From ΔM, it can be seen that the embodiment group M H and ΔM show a small increase, indicating that the degree of vulcanization of the rubber can be increased. As can be seen from Table 5, as the degree of vulcanization increases, the tensile strength and tear strength also increase accordingly.

[0102] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. Application of Gourd Tea Extract in Natural Rubber Processing.

2. A method for producing natural full latex rubber, characterized in that: The following steps are involved: The natural rubber latex, water and a water-soluble antioxidant are mixed and then acid coagulated to obtain a latex block; The latex block is sequentially thinned, creped and granulated to obtain latex particles; The rubber particles are immersed in a bottle gourd tea extract solution and then dried to obtain natural full latex rubber.

3. The method for producing natural full latex rubber according to claim 2, characterized in that: The water-soluble antioxidant includes one or more of sodium ascorbate, sodium D-isoascorbate and glycine.

4. The method for producing natural full latex rubber according to claim 2 or 3, characterized in that: The mass ratio of the dry rubber in the natural rubber latex to the water-soluble antioxidant is 100:0.2-2.

5. The method for producing natural full latex rubber according to claim 2, characterized in that: The mass percentage of the cucurbit tea extract in the cucurbit tea extract solution is 0.3-1%.

6. The method for producing natural full latex rubber according to claim 2 or 5, characterized in that: The soaking time is 0.05 to 4 minutes.

7. The method for producing natural full latex rubber according to claim 2 or 5, characterized in that: The preparation method of the bottle gourd tea extract comprises the following steps: The calabash tea is immersed in water for extraction to obtain an extract; The extract is concentrated and mixed with ethanol for extraction to obtain an organic phase; The organic phase is subjected to reduced pressure distillation to obtain the bottle gourd tea extract.

8. The method for producing natural full latex rubber according to claim 7, characterized in that: The leaching temperature is 95-100° C., and the leaching time is 25-35 minutes.

9. The method for producing natural full latex rubber according to claim 2, characterized in that: The acid solution includes a formic acid solution or an acetic acid solution; The mass concentration of the acid solution is 2.5-3.5%.

10. The method for producing natural full latex rubber according to claim 2 or 9, characterized in that: The solidification time is 14 to 18 hours.